2005
DOI: 10.2174/1570161053586912
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity from the Perspective of Oxidative Stress, Electron Transfer, and Prevention by Antioxidants

Abstract: This review demonstrates that oxidative stress, reactive oxygen species, and electron transfer can serve as unifying mechanistic themes for large numbers of cardiovascular toxins, both endogenous and exogenous. Lipid peroxidation is a prevalent insult. Common among the various conditions are atherosclerosis and arrhythmia. The preventive effects of antioxidants are documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 80 publications
0
36
0
1
Order By: Relevance
“…Indeed, most of these pathologies recognize multiple etiological factors, among which the detrimental role of oxidative stress has been stably recognized [12][13][14]. Moreover, it has been reported that creatine displays direct antioxidant activity both in acellular [15] and cellular systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most of these pathologies recognize multiple etiological factors, among which the detrimental role of oxidative stress has been stably recognized [12][13][14]. Moreover, it has been reported that creatine displays direct antioxidant activity both in acellular [15] and cellular systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Oxidative stress is associated with lipid peroxidation in lipoproteins and in arterial cells, including macrophages.3,4) These "oxidized macrophages" are characterized by increased peroxide levels, decreased glutathione content, and increased capability to oxidize lowdensity lipoprotein. 5,6) These properties of the cells increase their capability to accumulate cholesterol and to form macrophage foam cells.…”
mentioning
confidence: 99%
“…1,2) Oxidative stress is associated with lipid peroxidation in lipoproteins and in arterial cells, including macrophages.…”
mentioning
confidence: 99%
“…Electron donors consist of phenols, N-heterocycles or disulfides in proteins which produce relatively stable radical cations. ET, ROS, and OS have been increasingly implicated in the mode of action of drugs and toxins, (e.g., antiinfective agents [3], anticancer drugs [4], carcinogens [5], reproductive toxins [6], nephrotoxins [7], hepato-toxins [8], cardiovascular toxins [9], nerve toxins [10], mitochondrial toxins [11], abused drugs [12], pulmonary toxins [13], ototoxins [14], and various other categories [15].…”
Section: Introductionmentioning
confidence: 99%